Neutrophil extracellular traps exacerbate Th1‐mediated autoimmune responses in rheumatoid arthritis by promoting DC maturation. Issue 11 (5th October 2016) - Papadaki, Garyfalia; Kambas, Konstantinos; Choulaki, Christiana; Vlachou, Katerina; Drakos, Elias; Bertsias, George; Ritis, Konstantinos; Boumpas, Dimitrios T.; Thompson, Paul R.; Verginis, Panayotis; Sidiropoulos, Prodromos
Abstract : Factors in the inflammatory milieu of rheumatoid arthritis (RA) induce polymorphonuclear cells to undergo neutrophil extracellular trap formation. RA neutrophil extracellular traps serve as a source of neoantigens complexed with DNA to promote the activation and cytokine release by DCs, leading in the production of IFN‐γ by T cells. This cascade contributes in the RA autoimmune responses. Abstract : Aberrant formation of neutrophil extracellular traps (NETs) is a key feature in rheumatoid arthritis (RA) and plays a pivotal role in disease pathogenesis. However, the mechanism through which NETs shape the autoimmune response in RA remains elusive. In this study, we demonstrate that inhibition of peptidylarginine deiminases activity in collagen‐induced arthritis (CIA) mouse model significantly reduces NET formation, attenuates clinical disease activity, and prevents joint destruction. Importantly, peptidylarginine deiminase 4 blocking markedly reduces the frequency of collagen‐specific IFN‐γ‐producing T helper 1 (Th1) cells in the draining lymph nodes of immunized mice. Exposure of dendritic cells (DCs) to CIA‐derived NETs induces DC maturation characterized by significant upregulation of costimulatory molecules, as well as elevated secretion of IL‐6. Moreover, CIA‐NET‐treated DCs promote the induction of antigen‐specific Th1 cells in vitro. Finally, NETs from RA patients show an increased potential to induce the maturation of DCs from healthy individuals, corroborating the findings obtained in CIA mouse model. Collectively, our findings delineate an important role of NETs in the induction and expansion of Th1 pathogenic cells in CIA through maturation of DCs and reveal a novel role of NETs in shaping the RA‐autoimmune response that could be exploited therapeutically.